The Indigenization Strategies of Catholic Painting in Early 20th Century China - Zhang, Xinyi (Religions (Basel, Switzerland ), 2024)
The spread of Christianity to China initiated a process of indigenization, particularly evident in Christian art. This study explores the indigenization of early 20th-century Chinese Christian paintings through literature reviews, case studies, and comparative research. The analysis covers four forms of primary research. First, it explores the indigenization of Christian concepts, tracing their development from the introduction of Nestorian Christianity in the Tang dynasty through the establishment of Fu Jen Catholic University in the Republican era. Matteo Ricci’s implementation of the “Ricci Rule” during the late Ming dynasty, subsequently expanded by Celso Costantini, played a crucial role in the indigenous adaptation of Christian painting in China. The second facet focuses on the Beijing Catholic School of Painting, led by Chen Yuandu, a group that innovated Chinese Christian art by integrating local artistic expressions with traditional depictions of saints, assimilating symbols from Chinese literati painting, and preserving time-honored Chinese painting techniques. The third facet examines the strategy behind Christian painting methods. Fourth, this study discusses how the Fu Jen School faced varied reception and evaluations from domestic and international audiences under the complex social currents of the Republic of China and how the artists reflected the national spirit and artistic responsibility in their narrative paintings. Fundamentally, the practice of Christian painting at the early 20th-century Catholic School is not only an innovative artistic endeavor but also a significant case of cultural exchange between East and West and religious localization.